An attempt to write the life and biography of Yousef Yaskeh (1593-1630) - مورادی باقلاوایی ئیرەج (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The writing of kurdish history, especially the literary works of poets and scholars, has not yet been done in a unified manner due to the scattering of documents and writings. For example, Yousef Yaskeh is one of those poets. Yusuf also studied with Khan Ahmad Khan at Qala School. The poems of Yaskeh and Yousef have been recorded in the old Manuscript.Yusuf was a handsome boy, a good songwriter and dancer, and is known as the unrivaled master of Siachmaneh. In one of his poems, which he recites with his mother Yaskeh, he talks about his imprisonment in Khan Ahmad Khan prison. Historical sources have written about the love affair between this poet and Khan Ahmad Khan’s wife. He has been imprisoned for this reason. The love story of Yousef Yaskeh can be heard in Ardalan, Shahrzour and Horaman regions. The story of this lover is heard in different geographical areas and is seen in places such as the castle, mountain and tomb of Yousef Yaskeh in these areas. In this article, an attempt has been made to compile the life and biography of the famous poet Yousef Yaskeh according to documents, sources and oral traditions.